Post-COVID-19 patients' clinical-epidemiological characteristics in Baracoa, Guantánamo - Yirleidy Rodríguez Labañino; Yodanky Ochoa Rodríguez; Alexander Durán Flores; Denny Matos Laffita; Oneidis Durán Flores (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
Background: a high percentage of people who have suffered from COVID-19 report, after recovery from the acute phase, manifestations that last for more than three weeks, and even for three months after the original clinical picture. Objective: to characterize, from the clinical and epidemiological point of view, patients confirmed to SARS-CoV-2 in the post-COVID-19 stage. Methods: a descriptive cross-sectional study was carried out in patients confirmed to SARS-CoV-2 in the post-COVID-19 stage, belonging to the Hermanos Martínez Tamayo Polyclinic, from October to November 2021. All patients were studied (N= 400) attended in post-COVID-19 consultation in the declared period. The information was obtained through epidemiological surveys carried out. Results: there was a predominance of patients aged between 50 and 59 years old, female. The most frequent clinical manifestations were cough, loss of taste and smell. The incomplete vaccination scheme was the most frequent. The most used place of admission were isolation centers, as well as the use of Nasalferon as a treatment. Complications predominated in unvaccinated patients, and aged 60 years and over. Conclusions: a high percentage of patients presented clinical manifestations after the acute period of the disease. COVID-19, in the medium term, had greater implications in the respiratory, nervous and osteomyoarticular systems. Vaccination campaigns help prevent serious symptoms of the virus and counteract complications.